1982
DOI: 10.1104/pp.70.6.1605
|View full text |Cite
|
Sign up to set email alerts
|

Genome Expression during Normal Leaf Development

Abstract: The quantitative relationships between ribulose bisphosphate carboxylase, nuclear ploidy, and plastid DNA content were examined in the nonisogenic polyploid series Triticum monococcum (2X), Triticum dicoccum (4x), and Triticum aestivum (6x). Ribulose bisphosphate carboxylase per mesophyl cel increased in step with each increase in nuclear ploidy so the ratios of ribulose bisphosphate carboxylase per mesophyUl ceUl (picograms) to nuclear DNA per mesophyUl ceUl (picograms) were almost identical in the three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…This is in the range postulated (Molz and Boyer 1978) and reported (Boyer et al 1985) for growing hypocotyl tissue of soybean (however, see Malone and Tomos 1992). Provided that xylem Y was uniform along the zone (the vessel elements might have still been alive and contained end walls, Dean and Leech 1982), then the present results indicate that the resistance to water movement between xylem and expanding epidermal cell changed along the growth zone and limited growth most in Hoagland-plants ± maybe due to anatomical changes (number or length of epidermal, mesophyll and vessel-element cells; Dean and Leech 1982).…”
Section: What Reduces Ler In N-limited Barley Plants?mentioning
confidence: 83%
“…This is in the range postulated (Molz and Boyer 1978) and reported (Boyer et al 1985) for growing hypocotyl tissue of soybean (however, see Malone and Tomos 1992). Provided that xylem Y was uniform along the zone (the vessel elements might have still been alive and contained end walls, Dean and Leech 1982), then the present results indicate that the resistance to water movement between xylem and expanding epidermal cell changed along the growth zone and limited growth most in Hoagland-plants ± maybe due to anatomical changes (number or length of epidermal, mesophyll and vessel-element cells; Dean and Leech 1982).…”
Section: What Reduces Ler In N-limited Barley Plants?mentioning
confidence: 83%
“…10 7 Rubisco subunits [15], 106 Photosystem I, Photosystem II, ATP synthase and Cytochrome b6/f complexes [41], 10 4 to 10 5 ribosomes [28] to less t h a n 10 4 RNA polymerase complexes (unpublished data from this lab) per chloroplast. In general, the abundance of chloroplast-encoded proteins is correlated with their corresponding mRNA levels [49].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, transcriptional differences in several genes that are directly and indirectly involved in photosynthesis and starch metabolism had previously been reported between diploids and allotetraploid A. thaliana (Wang et al, 2006;Ni et al, 2009), and levels of the CO 2 -fixing enzyme Rubisco were reported to increase with an increase in ploidy in allopolyploid wheat (Triticum aestivum; Dean and Leech, 1982). However, allopolyploidy adds another complication in that organisms with genomic contributions from two or more species do not exhibit exclusively additive or predictably changing gene expression (Madlung et al, 2002;Wang et al, 2004;Chen, 2010;Matsushita et al, 2012).…”
mentioning
confidence: 96%